State accountability for space debris : a legal study of responsibility for polluting the space environment and liability for damage caused by space debris - Stubbe, Peter (Jurist) (Studies in space law ;, 2017)
In State Accountability for Space Debris Peter Stubbe examines the legal consequences of space debris pollution -- which he argues is a global environmental concern -- under the two distinct accountability regimes of responsibility and liability.--